SIFAT-SIFAT PAPAN KOMPOSIT DARI SABUT KELAPA, LIMBAH PLASTIK DAN PEREKAT UREA FORMALDEHIDA - dina Setyawati; Sondang M. Sirait; Dewi Rahmaniah (Universitas Tanjungpura, 2012)
The objective of this research was to evaluate the characteristic of composite boards made from coir, plastic waste , and urea formaldehyde (UF). The board samples were manufactured at target density of 0,7 gr/cm3. The weight ratio of waste plastic and coir was 50: 50. the UF adhesive added at 0%, 4%, 8%, 12% and 16% of the total weight of the composite board. The result shows that the characteristic of composite boards improve with UF adhesive added, however no signifivant difference was found statistically. Key words : Choir, plastic waste, UF, composite board, physical and mechanical properties